Individual Creativity and Group Ability to Utilize Individual Creative Resources: A Multilevel Model - Taggar, Simon (Academy of Management Journal, 2002)
The performance of 94 groups on 13 different open-ended tasks was studied. At the individual-team-member level, domain knowledge and performance-relevant behavioral measures of the three components of Amabile's (1983, 1996) theory of individual creativity related in predicted ways to individual differences. Support was found for new ?cross-level? processes, labeled ?team creativity-relevant processes.? At the group level, these processes moderated the relationship between aggregated individual creativity and group creativity.